Characterization of infectious bronchitis viruses isolated from commercial poultry farms in Malaysia - Khanh, Nguyen Phuc; Tan, Sheau Wei; Yeap, Swee Keong; Satharasinghe, Dilan Amila; Bejo, Mohd Hair; Omar, Abdul Rahman (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Infectious bronchitis virus (IBV) primarily causes a highly infectious bronchitis (IB) disease in commercial chickens. Virus isolation and identification is necessary for diagnosis of the disease. A total of 6 IBV isolates from commercial poultry farms in Malaysia were isolated by inoculation in 9 day-old embryonated SPF eggs. After few passages, the embryos showed typical lesions of IB such as stunted and curled cross with feather dystrophy. The isolated IBV were characterized by RT-PCR followed by DNA sequencing of partial S1 gene. Sequencing and phylogenetic analysis showed that all the IBV isolates can be divided into 2 distinct groups. In group I (IBS037A, IBS037B, IBS051 and IBS052) shared 70% similarity with Group II (IBS130 and IBS131). However, group II viruses were genetically closed to QX-like IBV isolates with similarity of 93%. Meanwhile, Group I that formed a distinct branch of the phylogenetic tree has genetic distance ranged from 30% to 36% with 793/B, Mass-type, Taiwan-type and QX-like viruses.